Generalizability of HFA-PEFF and H2FPEF Diagnostic Algorithms and Associations With Heart Failure Indices and Proteomic Biomarkers: Insights From PROMIS-HFpEF - Faxen, U. L. (Elsevier B.V., 2022)
10.1016/j.cardfail.2021.02.005